On the relationship between filaments and solar energetic particles. (November 2018) - Tsvetkov, Ts; Miteva, R.; Petrov, N.
Abstract: In the current study the association rate between solar energetic particles (protons) and filaments and/or filament eruptions (FEs) is investigated using the largest reported event sample. Proton events observed in the period 2010–2016 are accompanied by filaments in 92% (143/156) of the cases. Due to the lack of comprehensive catalog of all filaments, a catalog of FEs is used for the reversed association. Only 5% of FEs have in situ proton signatures with larger peak intensity, compared to the median of the entire proton sample. Other solar activity phenomena (flares and coronal mass ejections) related to the proton events show differences in their distributions compared to the respective FE-samples. The indication for a shock wave formation using the type II radio signatures is also considered and discussed. Highlights: Filament-related proton events are slightly more common than non-related (53/47 %). The majority of the proton events originate from the western hemisphere (≈70 %). 87% of solar energetic particle-related ﬁlaments are localized in active regions. Only 5% of the eruptive ﬁlaments tend to produce proton events.